GROUNDWATER CHARACTERISTICS ASSESSMENT IN KURDISTAN REGION PROVINCES-IRAQ: A REVIEW - HAWEZ, DARA MUHAMMAD; MIZZOURI, NASHWAN SHAWKAT; AZIZ, SHUOKR QARANI; MUSTAFA, JWAN SABAH; MANGURI, SHWANA BRAIM HASSAN (Journal of Duhok University, 2021)
Over the past decades, drilling wells and groundwater extraction for agricultural, domestic, and industrial purposes is growing at a high rate in Kurdistan Region-Iraq, meaning that groundwater becomes one primary water source. Increased demand for water and over-exploitation and unsustainable practices severely deteriorate groundwater. Therefore, it is essential to monitor the water quality. In the past years, many papers have been published on groundwater quality in the Kurdistan Region. Thus, this research aims to review, evaluates and summarizes the results of published papers concerning groundwater characteristics in Erbil, Suliamni, Duhok, and Halabja, Governorates. This work targets about thirty published papers. These papers focused on Wells, Springs, and karizes (qanats) as groundwater. The water testes have taken from different cities and locations in these three governorates. The reviewed studies considered a number of water parameters and chemical elements, such as physicochemical parameters, heavy metals, and radioactive substances. This work assesses water quality parameters from reviewed studies and illustrates the comment parameters by the spatial distribution mapped using the kriging method. Generally, the groundwater polluted in some zones in the Kurdistan Region and normally it can be used for drinking and domestic uses after the disinfection process.